Cajatambo: tradítíon, quechua and regional disintegration - Miranda Valdivia, Franklin (2011)
The ancestral province of Cajararnbo, nestled in thc Andean region of Lima, has a disranr and deep hisrorical roots rhan marks thcir strong rradition from the pro-Inca era, quechua. inca, colonial and Republican era. Ir passes rhrough its history insritutions sueh as rhc ayllu, rhe encomienda, thc reductions, rhe obrajes, colonial parry and during rhe Republic appcars rhe province, Subsequently the decades of rhe 60's and the 70's of thc 20th century rhe rural migration is intensc and is canditioned by the agrarian crisis, rhc culrnination uf [he road and rhe increase in hispanic schooling on one hand, ando on rhc orher hand, ihe systernaric reducdon and territorial disrnernbermenr rhat occurred in rhe Republic. These processes of regional disinregration of rhe rural structure and weaken of rhc quechua of this region. show trough the highest provincial poverry (60.7%) and rhe 85% of disuíct poveny of Copa and Gorgor. Even so rhe Quechua language ís spoken by 14.2 per cent of írs populauon, Becausc of that as living expression of rhe cultural diversiry uf Cajatambo requires to be rescued, preserved and prornored in his oraliiy, in which rhe role of women and rhe eldcrly peoplc wcre and are a guaranrce for its conrinuiry,